2007
DOI: 10.1016/j.ygeno.2007.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling in the adult Down syndrome brain

Abstract: The mechanisms by which trisomy 21 leads to the characteristic Down syndrome (DS) phenotype are unclear. We used whole genome microarrays to characterize for the first time the transcriptome of human adult brain tissue (dorsolateral prefrontal cortex) from seven DS subjects and eight controls. These data were coanalyzed with a publicly available dataset from fetal DS tissue and functional profiling was performed to identify the biological processes central to DS and those that may be related to late onset path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
173
0
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(203 citation statements)
references
References 65 publications
26
173
0
4
Order By: Relevance
“…We see widespread differential expression of genes from the other diploid chromosomes (Fig. 2B), consistent with the results of Gardiner (37) and Lockstone et al (29). Hierarchical clustering of our samples based on expression levels of the 409 Individual genes not located on chromosome 21 completely separates the DS samples from the controls (as seen in Fig.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We see widespread differential expression of genes from the other diploid chromosomes (Fig. 2B), consistent with the results of Gardiner (37) and Lockstone et al (29). Hierarchical clustering of our samples based on expression levels of the 409 Individual genes not located on chromosome 21 completely separates the DS samples from the controls (as seen in Fig.…”
Section: Discussionsupporting
confidence: 91%
“…Because individuals with DS demonstrate pathology consistent with Alzheimer disease at an early age (28), links to the role of oxidative stress in Alzheimer's have been explored (27). Lockstone et al (29) found that oxidative stress response genes were over-represented in adult but not fetal DS tissue, and suggested that this response might reflect adult-onset DS pathologies such as Alzheimer disease. More recently, a few groups (16,30) have found oxidative stress response markers in fetal DS tissues, although neither study emphasized this particular result or considered the potential relationship between oxidative stress and other functional pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, our data may be also relevant for studies of Down syndrome (DS). Indeed, DYRK1A is one of the genes located in the Down syndrome critical region (Delabar et al, 1993) and its expression is upregulated in DS individuals (Dowjat et al, 2007;Lockstone et al, 2007). Notch signalling is also altered in the DS condition, although contrasting data have been obtained in studies in humans and mouse models.…”
Section: Dyrk1a Attenuates Notch Signalling In Vivomentioning
confidence: 99%
“…Additionally, it is important that in most instances, a complete triplication of genes located on chromosome 21 may dominate genes commonly dysregulated in DS and AD [29]. Also, the number of brain tissue samples samples profiled in microarray experiments was by far the lowest among other types of NDG diseases investigated in our survey.…”
Section: Resultsmentioning
confidence: 95%